Screening underground structures from ground vibrations due to a mass vibrator - Koh, Teck Wei (2015)
Ground vibrations due to human activity can be reduced with the installation of seismic barrier within the soil. In this report, the possibility of using a seismic barrier for a structure underground to reduce the impact of soil vibration on the structure was investigated. A series of field tests using a mass vibrator to examine the damping effect of a seismic barrier made of soilrubber mixtures was carried out. The outcome from these experimental studies can be briefly generalized as follows: The protective layer does reduce the amplitude of vibration experienced by the structure, and the reduction increases exponentially as the rubber content increases.